2023
DOI: 10.1080/22221751.2023.2220578
|View full text |Cite|
|
Sign up to set email alerts
|

A one-year follow-up study of systematic impact of long COVID symptoms among patients post SARS-CoV-2 omicron variants infection in Shanghai, China

Abstract: Long COVID hinders people from normal life and work, posing significant medical and economic challenges. Nevertheless, comprehensive studies assessing its impact on large populations in Asia are still lacking. We tracked over 20,000 patients infected with COVID-19 for the first time during the Omicron BA.2 outbreak in Shanghai from March-June 2022 for one year. Of the 21,799 COVID-19 patients who participated in the 6-month telephone follow-up, 1939 (8.89%) had self-reported long COVID symptoms. 450 long COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
5
19
0
Order By: Relevance
“…Recovery from liver damage has also been shown to be one of the hallmarks of survival in critically ill patients 23 . The results were consistent with a previous report that ~9% of moderate-severe BA.2 infection may lead to symptomatic long COVID at six months post BA.2 infection 13 . Additionally, Age and RNAemia were reported to be the best binary signatures associated with 28-day ICU mortality 23 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Recovery from liver damage has also been shown to be one of the hallmarks of survival in critically ill patients 23 . The results were consistent with a previous report that ~9% of moderate-severe BA.2 infection may lead to symptomatic long COVID at six months post BA.2 infection 13 . Additionally, Age and RNAemia were reported to be the best binary signatures associated with 28-day ICU mortality 23 .…”
Section: Discussionsupporting
confidence: 93%
“…This also suggests that a balance between immunity and metabolism is required for complete recovery. Additionally, in the absence of obvious symptoms, we do not recommend using any drug to correct the immunity-metabolism imbalance as major manifestations of long COVID caused by mild BA.2 BTI were induced by abnormal mental state 13 . But coagulation disorder should be kept an eye on, and the prolactin level can be interfered with if retained too high, especially for male patients, which can not only reduce inflammation to a certain extent but also relieve related long-term complications.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One study showed that the prevalence of long COVID was between 10% and 15%, 24 and a previous study from China showed that 8.89% of infected individuals self-reported long COVID symptoms, 25 which is basically consistent with the results of our study (9.73%). However, other studies have reported different prevalence rates.…”
Section: Discussionsupporting
confidence: 92%